Optimisation Regarding Local Stability and Strength of Long Multilayered Plates Subjected to Compression - Królak, M.; Kowal-Michalska, K.; Świniarski, J. (Engineering Transactions, 2003)
In this paper the method of optimal selection of orthotropic layers thickness is presented. The considerations concern long rectangular plates subjected to uniform compression in the direction of longer edges. Such plates (or cylindrical panels) of increased local buckling resistance could be applied as components of thin-walled columns of closed cross-sections.